Thermally reduced kaolin-graphene oxide nanocomposites for gas sensing - Zhang, Renyun (Sci Rep, 2015)
Highly sensitive graphene-based gas sensors can be made using large-area single layer graphene, but the cost of large-area pure graphene is high, making the simpler reduced graphene oxide (rGO) an attractive alternative. To use rGO for gas sensing, however, require a high active surface area and slightly different approach is needed. Here, we report on a simple method to produce kaolin-graphene oxide (GO) nanocomposites and an application of this nanocomposite as a gas sensor. The nanocomposite was made by binding the GO flakes to kaolin with the help of 3-Aminopropyltriethoxysilane (APTES). The GO flakes in the nanocomposite were contacting neighboring GO flakes as observed by electron microscopy. After thermal annealing, the nanocomposite become conductive as showed by sheet resistance measurements. Based on the conductance changes of the nanocomposite films, electrical gas sensing devices were made for detecting NH(3) and HNO(3). These devices had a higher sensitivity than thermally annealed multilayer GO films. This kaolin-GO nanocomposite might be useful in applications that require a low-cost material with large conductive surface area including the demonstrated gas sensors.